Shell Colour Diversity in Marine Molluscs: From Current Knowledge to Future Aquaculture Applications - Biyang Hu; Hong Yu; Chengxun Xu; Lingfeng Kong; Shikai Liu; Qi Li (Reviews in Aquaculture, 2025)
Mollusc shell colour represents an important economic trait contributing to product marketability in aquaculture. Marine molluscs with diverse shell colours and patterns are valuable models for animal colouration mechanisms study. Recent progress in marine mollusc shell colour research has been propelled by investigations of shell‐colour variants, advancements in high‐throughput sequencing technologies, and research into metabolic regulatory mechanisms for pigment biosynthesis. This review synthesizes current advancements in genetic architecture, gene regulatory networks and pigment metabolic processes governing shell colour variation in marine molluscs. In this review, insights gained from genetic studies uncover diverse inheritance patterns, key loci and present shell‐colour‐related transcriptomic datasets along with integrative multi‐omics studies. Moreover, distribution, metabolic networks and functional gene linkages of major pigments (melanin, carotenoids, and porphyrins) are characterized, while ommochromes are also discussed. Furthermore, environmental, dietary and structural factors influencing shell colour are listed. By synthesizing current findings, this review offers a detailed overview of the common factors influencing shell colour across marine mollusc species and probes the potential implications of shell colour studies for aquaculture. Future research directions emphasize pigment characterization, pigment transport mechanism studies and integrative multi‐omics approaches to bridge genetic and chemical understandings. In summary, this review outlines the current progress on marine mollusc shell colouration, provides referable research directions on shell‐colour‐related molluscs, and enhances understanding of animal colouration mechanisms.

Genetic improvement of oysters: Current status, challenges, and prospects - Kunyin Jiang; Chen Chen; Gaowei Jiang; Yong Chi; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Reviews in Aquaculture, 2024)
Oysters are one of the most commercially important shellfish species and have been cultured for thousands of years. Oyster aquaculture supports the major aquaculture industries in many countries. Over the last few decades, the oyster breeding and aquaculture industries have developed rapidly to meet the continually growing demand. Many researchers have made significant efforts toward the genetic improvement of commercially important traits in oysters. Some strains with fast‐growing, disease‐resistant, and stable shell‐colours have been developed through selective breeding. Some hybrid varieties have been developed by crossing different geographical populations or cultivated strains. Several hybrids exhibit considerable genetic variation and improved productive performance. Additionally, polyploid induction technologies have been applied in the oyster aquaculture industry, which provides a useful tool for performance improvement and genetic containment of cultured stocks. At present, the development of molecular breeding also provides a great opportunity for oyster genetic improvement. These advances in oyster breeding have improved the quality of oysters, brought great economic benefits, and been conducive to the sustainability of oyster production. Nonetheless, there are still some limitations and obstacles in oyster breeding, such as infectious diseases, summer mortality, conservation of germplasm resources, environmental contamination, and climate change. The present review provides an overview of the current status, challenges, and prospects in oyster breeding.

Estradiol‐17β and testosterone levels in the cockle Fulvia mutica during the annual reproductive cycle - Wenguang Liu; Qi Li; Lingfeng Kong (New Zealand Journal of Marine and Freshwater Research, 2008)
In this study, we investigated seasonal variations in the concentrations of estradiol‐17β (E 2 ) and testosterone (T) in the gonad of the cockle Fulvia mutica from March 2004 to February 2005 in relation to the reproductive cycle. Histological data showed that F. mutica is a hermaphrodite bivalve species, and gametogenesis took place during winter‐spring (November‐April) and spawning occurred in summer (May‐June) when water temperature was higher. E 2 and T concentrations were measured by enzyme‐linked immunosorbent assay (ELISA). E 2 concentrations varied between 7.27 and 32.63 pg/g wet weight and T concentrations ranged from 22.83 to 77.15 pg/g wet weight throughout the year. Both steroids exhibited a similar annual pattern that correlated with the reproductive cycle. The two peaks of E 2 and T concentrations in November and May‐June occurred at critical moments of the F mutica reproductive cycle: the onsets of gametogenesis and of the spawning period. E 2 andT concentrations were low during the non‐reproductive period extending from July to October. These results suggest that E 2 and T could play a role as endogenous modulators in the reproductive cycle of F. mutica .